FABRICATION OF TiO2 BASED COMPOSITE MATERIALS BY HYDROTHERMAL METHOD - Canbay, Canan Aksu; Özbey, Furkan (Murat Yakar, 2020)
Composite nanoparticles (nano powders) are nano-sized and can be synthesized with a wide range of organic, inorganic materials and production techniques. Titanium dioxide is one of the most commonly used materials in the production of composite materials. The reason why titanium dioxide is more preferred is that it has a minimum of any reactive step, it does not interfere with the human body and is an organic material that does not contain by-products. The photocatalytic properties of titanium dioxide can be improved by various methods. TiO2 is the most widely used photocatalyst in air purification. In this study, titanium dioxide based composite material was fabricated by hydrothermal method. The electrical, optical and structural properties of the material were investigated with the contribution of three different compositions of cadmium oxide (CdO) for produced in the experiments. For this purpose, SEM, U-V (Vis), I-V and FTIR techniques were used for the characterization and obtained results evaluated. © 2020, Murat Yakar. All rights reserved.
Keywords: CdO; Composite Material; Hydrothermal Method; TiO2